Glycation potentiates neurodegeneration in models of Huntington's disease - Miranda, Hugo Vicente (2017)
Protein glycation is an age-dependent posttranslational modification associated with several neurodegenerative disorders, including Alzheimer's and Parkinson's diseases. By modifying aminogroups, glycation interferes with folding of proteins, increasing their aggregation potential. Here, we studied the effect of pharmacological and genetic manipulation of glycation on huntingtin (HTT), the causative protein in Huntington's disease (HD). We observed that glycation increased the aggregation of mutant HTT exon 1 fragments associated with HD (HTT72Q and HTT103Q) in yeast and mammalian cell models. We found that glycation impairs HTT clearance thereby promoting its intracellular accumulation and aggregation. Interestingly, under these conditions autophagy increased and the levels of mutant HTT released to the culture medium decreased. Furthermore, increased glycation enhanced HTT toxicity in human cells and neurodegeneration in fruit flies, impairing eclosion and decreasing life span. Overall, our study provides evidence that glycation modulates HTT exon-1 aggregation and toxicity, and suggests it may constitute a novel target for therapeutic intervention in HD.